Implementasi Tindak Pidana Jual Beli Organ Ditinjau dari Frasa Kompensasi Donor yang Diperbolehkan Menurut Sistem Hukum di Indonesia - Chatrina Aprilia (LPPM Universitas Ekasakti Padang, 2023)
Organ transplantation is the transfer of all or part of an organ from one body to another, or from one part to another part of the same body. Organ donors can come from people who are still alive or have died. This research describes and examines the first problem, how the legal relationship between donors and recipients of donors in living organ transplants in providing compensation is allowed according to applicable law in Indonesia. This research is a descriptive doctrinal legal research. the sources used are primary legal materials consisting of legal products such as laws, and other relevant legal regulations related to organ transplants. The result of this research is that the legal relationship between the donor and the recipient of the donor is a natural engagement that occurs due to urgent needs in the process before the implementation of Organ Transplantation. The implementation of organ transplantation is carried out by prioritizing a sense of volunteerism in donating organs without asking for compensation so that the phrase from the word compensation in this case is the payment of handling costs during the donor's treatment in the hospital both before, during and after surgery this is based on the Minister of Health Regulation Number 38 of 2009 concerning the Implementation of Organ Transplantation to complete and reaffirm organ transplantation is carried out voluntarily, within the scope of the hospital at all stages